The impact of technology on external competitiveness in the Caribbean, Latin America and South America - Grenade, Kari ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Provides empirical estimates of the impact that technology can have on external competitiveness. Evaluates whether different components of technology are more relevant that others.